Buttons-on-demand using shape memory alloys - Tan, Darius Jia Qing (Nanyang Technological University, 2024)
In many situations or vehicles that require focus and attention, control boards that are complicated and have too many buttons that distract and occupy its users longer than it should be to find the button that they require can have a negative outcome. The concept of buttons-on-demand is applied to reduce the users distraction and also enhances users experience by reducing the cluster of buttons. This final year project “Buttons-on-demand using shape memory alloys” focuses on using smart materials to automate functions and simplifying the mechanism. The objective is to implement a new mechanism and make it simple.